Dementia severity and the longitudinal costs of informal care in the Cache County population. Issue 8 (19th January 2015) - Rattinger, Gail B.; Schwartz, Sarah; Mullins, C. Daniel; Corcoran, Chris; Zuckerman, Ilene H.; Sanders, Chelsea; Norton, Maria C.; Fauth, Elizabeth B.; Leoutsakos, Jeannie‐Marie S.; Lyketsos, Constantine G.; Tschanz, JoAnn T.
Abstract: Background: Dementia costs are critical for influencing healthcare policy, but limited longitudinal information exists. We examined longitudinal informal care costs of dementia in a population‐based sample. Methods: Data from the Cache County Study included dementia onset, duration, and severity assessed by the Mini‐Mental State Examination (MMSE), Clinical Dementia Rating Scale (CDR), and Neuropsychiatric Inventory (NPI). Informal costs of daily care (COC) was estimated based on median Utah wages. Mixed models estimated the relationship between severity and longitudinal COC in separate models for MMSE and CDR. Results: Two hundred and eighty‐seven subjects (53% female, mean (standard deviation) age was 82.3 (5.9) years) participated. Overall COC increased by 18% per year. COC was 6% lower per MMSE‐point increase and compared with very mild dementia, COC increased over twofold for mild, fivefold for moderate, and sixfold for severe dementia on the CDR. Conclusions: Greater dementia severity predicted higher costs. Disease management strategies addressing dementia progression may curb costs.